2020
DOI: 10.1144/jgs2020-089
|View full text |Cite
|
Sign up to set email alerts
|

Outcrop-scale manifestations of reactivation during multiple superimposed rifting and basin inversion events: the Devonian Orcadian Basin, northern Scotland

Abstract: The Devonian Orcadian Basin in Scotland hosts extensional fault systems assumed to be related to the initial formation of the basin, with only limited post-Devonian inversion and reactivation. However, a recent detailed structural study across Caithness, underpinned by published Re–Os geochronology, shows that three phases of deformation are present. North–south- and NW–SE-trending Group 1 faults are related to Devonian ENE–WSW transtension associated with sinistral shear along the Great Glen Fault during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…1; Allan and Mange-Rajetzki, 1992; Duncan and Buxton, 1995). It should be noted that, strictly speaking, the Clair Group formed in an adjacent basin, in a somewhat different tectonic setting (Dichiarante, 2017;Dichiarante et al, 2020a).…”
Section: Location and Regional Structurementioning
confidence: 99%
See 3 more Smart Citations
“…1; Allan and Mange-Rajetzki, 1992; Duncan and Buxton, 1995). It should be noted that, strictly speaking, the Clair Group formed in an adjacent basin, in a somewhat different tectonic setting (Dichiarante, 2017;Dichiarante et al, 2020a).…”
Section: Location and Regional Structurementioning
confidence: 99%
“…Deformation bands, gouges and breccias associated with these faults display little or no mineralization or veining. It is suggested that these structures are related to Devonian ENE-WSW transtension associated with sinistral shear along the Great Glen Fault during formation of the Orcadian and proto-West Orkney basins (Wilson et al, 2010;Dichiarante et al, 2020a). Wilson et al (2010) and the trace of the regional-scale transects (WTR1 and WTR2) and the location of the sub-regional transects (DO and SJ).…”
Section: Location and Regional Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Fault-slip slickenline data associated with each of the mineralized fault groups identified in the field were used to carry out a conventional palaeostress inversion analysis (Angelier 1979(Angelier , 1984Michael 1984) implemented using MyFault® software following the protocols set out by Holdsworth et al (2015) and Dichiarante et al (2020). Importantly, any analysis of this kind is viable only in regions where finite strains are modest and the presence of major fault block rotations can be ruled out.…”
Section: Stress Inversion Analysismentioning
confidence: 99%